FROM WORKAHOLISM TO BURNOUT: AN INCLUSION OF PSYCHOLOGICAL CAPITAL - Moyer, Fiona E (East Carolina University, 2016)
In the current study we sought to examine the relationships among workaholism, psychological capital (PsyCap), and burnout. According to previous research, the incidence of workaholism is increasing in the United States. While these employees may, at first, reap benefits from their obsessive and highly involved tendencies, workaholic behavior has been shown to lead to a number of detrimental consequences to the employee and the organization. Thus, it is imperative that research be conducted to alleviate the consequences of the syndrome. Therefore, in the current study we sought to determine whether the presence of a positive personal resource, PsyCap, has the ability to weaken the relationship between workaholism and burnout. A sample of faculty and staff at a large Southeastern university were asked to complete three self-report measures of the main study variables. Results confirmed findings from previous research with regard to the correlational relationships among the variables. However, the results failed to support a moderating effect of PsyCap on the relationship between workaholism and burnout. Organizational implications of these findings and avenues for future research were discussed.
Keywords: Psychological Capital; Occupational Health Psychology; Industrial/Organizational Psychology; Workaholism--United States; Burn out (Psychology); Work--Psychological aspects; Positive psychology